2020
DOI: 10.1177/1010539520937091
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Conditions in Young Asian Adults and Motivation to Seek Counseling: A Cross-Country Study

Abstract: Mental illness is a prevalent and pressing public health problem among the Asian population, especially among young adults. This study examined the psychosocial predictors of the intention to seek counseling based on the theory of planned behavior (TPB) and the effects of mental health conditions on the relative contributions of the TPB predictors in forming the intention among Asian young adults. The survey results in Singapore (n = 232) and Hong Kong (n = 998) revealed that attitudes, descriptive no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Kim et al [33] found that students who showed symptoms of depression or significant psychological distress were less likely to recognize depression in a case vignette and also less likely to recommend help-seeking, compared to students without mental health problems. Shi et al [57] reported similar findings from students in Singapore and Hong Kong: Young Asian adults had overall low intentions to seek help for mental health problems. Students with worse mental health conditions were more reluctant to seek help and had less favorable attitudes towards counseling, compared to students with better mental health.…”
Section: Recognition Of Mental Disorders and Help-seeking Intentionsmentioning
confidence: 74%
“…Kim et al [33] found that students who showed symptoms of depression or significant psychological distress were less likely to recognize depression in a case vignette and also less likely to recommend help-seeking, compared to students without mental health problems. Shi et al [57] reported similar findings from students in Singapore and Hong Kong: Young Asian adults had overall low intentions to seek help for mental health problems. Students with worse mental health conditions were more reluctant to seek help and had less favorable attitudes towards counseling, compared to students with better mental health.…”
Section: Recognition Of Mental Disorders and Help-seeking Intentionsmentioning
confidence: 74%
“…Moreover, perceived behavioral control is linked to self-efficacy, the belief in one’s ability to seek psychological services. Shi et al (2020) demonstrated that individuals with severe mental health symptoms have lower perceived self-efficacy in seeking help, indicating that self-efficacy strongly influences the willingness to seek psychological care.…”
Section: Professional Mental Health Help-seeking Among Asian Americansmentioning
confidence: 99%
“…Shi et al consider mental illness is indeed a "prevalent and pressing" public health concern in Asia. 1 The author adds to the findings that in order to help those who are experiencing mental health problems, institutions should develop a large-scale support system and intervention hotlines that will cater the needs of people who are experiencing anxiety, psychological stress, and posttraumatic stress disorder. The World Health Organization once called upon Southeast Asian countries to pay attention to mental health and suicide prevention.…”
mentioning
confidence: 99%